Simulation of the machined surface after end milling with self-oscillations - Dyadya, S.; Kozlova, Ye.; Germashev, A.; Logominov, V. (Національний технічний університет "Харківський політехнічний інститут", 2021)
Thin-walled parts are widely used in the aviation industry. It is mainly carried out with end mills and is accompanied by self-oscillation during rough milling.They negatively affect the quality of the machined surface. Therefore, it is important to model it taking into account the dynamics of the milling process to predict the accuracy. In the early works of the authors, the mechanism of the profile forming of the machined surface was determined. In this case, the identity of the shape of the cutting surface and the oscillogram of part’s oscillations during milling is taken as a basis. The first wave of self-oscillations takes part in the shaping of the machined surface during cut-up milling with self-oscillation, and during cut-down milling - the last wave. The change in the distances of the cut depressions to the position of the elastic equilibrium of the part is periodically repeated from the maximum value to the minimum. Based on this, when modeling the waviness pitch of the machined surface after cut-up milling, it is necessary to know the feed rate and how many cuts were made by the tool from the largest to the smallest depression. When modeling the machined surface after cut-down milling, you need to know the length of the cutting surface. It is calculated based on cutting speed and cutting time. The formula for determining the waviness pitch after cut-down milling is derived taking into account the tool feed. The waviness height of the machined surface after cut-up and cut-down milling is determined as the difference between the largest and smallest depressions. To determine the size of the pitch and the height of the waviness, formulas are derived for converting electrical and time values of oscillograms into linear ones. These formulas also allow you to determine areas of the oscillogram with oscillations of the part during cutting and the resulting surface areas on the profilogram. The methods for modeling machined surfaces were tested after cut-up and cut-down milling with self-oscillation. In this case, the pitch and height of the waviness on the profilograms were compared with those calculated from the results of measurements of the oscillograms. Based on their analysis, refined formulas for calculating the waviness height have been derived. The error between the measurements of the waviness pitch and height and the calculated values is within 6%.

В авіаційній промисловості широко поширена обробка тонкостінних деталей. Переважно вона виконується кінцевими фрезами і при чорновому фрезеруванні супроводжується автоколиваннями. Вони негативно впливають на якість обробленої поверхні. Тому важливим є її моделювання з урахуванням динаміки процесу фрезерування для прогнозування точності. У ранніх роботах авторів визначено механізм формування профілю обробленої поверхні. При цьому за основу взята ідентичність форми поверхні різання і осцилограми коливань деталі при фрезеруванні. У формоутворенні обробленої поверхні при зустрічному фрезеруванні з автоколиваннями бере участь перша хвиля автоколивань, при попутному фрезеруванні - остання хвиля. Зміна відстаней вирізаних западин до положення пружної рівноваги деталі періодично повторюється від найбільшого значення до найменшого. На підставі цього, при моделюванні кроку хвилястості обробленої поверхні після зустрічного фрезерування, необхідно знати величину подачі і кількість різів, що зроблено інструментом від найбільшої до найменшої западини. При моделюванні обробленої поверхні після попутного фрезерування треба знати довжину поверхні різання. Вона розраховується на підставі швидкості різання і часу формування поверхні різання. Формула для визначення кроку хвилястості після попутного фрезерування отримана з урахуванням подачі інструменту. Висота хвилястості обробленої поверхні після зустрічного і попутного фрезерування визначається як різниця між найбільшою і найменшою западинами. Для визначення розмірів кроку і висоти хвилястості отримано формули по перетворенню електричних і часових величин осцилограм в лінійні. Ці формули також дозволяють визначати ділянки осцилограми з коливаннями деталі при різанні і отримані при цьому ділянки поверхні на профілограмі. Методики моделювання оброблених поверхонь перевірялися після зустрічного і попутного фрезерування з автоколиваннями. При цьому порівнювалися крок і висота хвилястості на профілограмі і розраховані за результатами вимірювань осцилограм. На підставі їх аналізу виведені уточнені формули для розрахунку висоти хвилястості. Похибка між результатами вимірювань кроку і висоти хвилястості і розрахованими значеннями знаходиться в межах 6%.
Моделювання обробленої поверхні після кінцевого фрезерування з автоколиваннями
Keywords: waviness; pitch; height; cutting surface; хвилястість; крок; висота; поверхня різання